Pozzolanic Behavior of Mt. Pinatubo Ejecta Under Natural and Accelerated Curing Condition - Jorillo Jr., Pablo A.; Verdejo, Benjamin D. (Philippine Engineering Journal; Vol 16 No 1 (1995), 2021)
This paper describes the results of the study on the evaluation of the pozzolanic behavior of Mt. Pinatubo ejecta under natural and accelerated curing conditions. The study is essentially a developmental research aimed in providing a comprehensive characterization of the volcanic ejecta in comparison with the local fly-ash. Two types of accelerated curing were examined viz., high pressure steam curing and boiling-cooling method. Various types of ejecta materials and percentage cement replacements were investigated to determine the optimum type and proportion in a cement based mortar matrix based on the criteria of strength and dimension stability.